2020
DOI: 10.1136/bmjopen-2020-039894
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and disease burden of complex wounds for inpatients in China: an observational study from Sichuan province

Abstract: ObjectivesTo investigate the period prevalence of complex wounds among the overall inpatients, and the impact of complex wounds on inpatient health expense and length of hospital stay (LOS).DesignAn observational study.Setting6056 healthcare institutions across Sichuan province in China.ParticipantsThis study included 4 033 763 people admitted to healthcare institutions during 1 September 2018 and 31 December 2018.ResultsThe point prevalence of complex wounds was 4.07 per 1000 among inpatients in Sichuan. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…A plausible explanation for this could be that those studies reported the prevalence of wounds from inpatient settings, where patients may be bed bound to a higher extent, whereas this primary care setting study included patients that are ambulant and more independent. 5 , 33 , 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible explanation for this could be that those studies reported the prevalence of wounds from inpatient settings, where patients may be bed bound to a higher extent, whereas this primary care setting study included patients that are ambulant and more independent. 5 , 33 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…This is rather unusual as patients with chronic wounds most frequently reported lower HRQoL in the domains related to physical functioning 13 and most patients with chronic wounds are retired. 44,45 This may indicate that chronic wound patients treated in primary care are younger compared to those in hospitals in Singapore. 5,33 The most common wound aetiologies in the present study were atypical hard-to-heal wounds and DFUs.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the United Kingdom analysed 11 years' worth of data (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) and found an annual national cost of over £2 billion for the treatment of VLUs [5]. A study in the Sichuan province in China found a point prevalence for VLUs of 0.28 per 1000 population [6], and this is likely an underestimate as it only considers hospital in-patients. In Australia, models suggest that over 300,000 people will be affected by VLUs, with the total cost over 5 years of treatment reaching between 1.2 and 2.8 billion AUD [7].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Management of the multiple causes of VLUs is an interdisciplinary challenge with major socio‐economic significance. 3 , 4 Patients with VLUs concurrently experience various psychoneurological symptoms including leg swelling, skin irritation, itchiness, pain, depression, fatigue, anxiety, and sleep disturbance. 5 , 6 , 7 , 8 Psychoneurological symptoms and the long‐term continuation of the condition not only affect patients' quality of life but also limit disease self‐management, functional status, and work patterns; indeed, many patients resort to early retirement.…”
Section: Introductionmentioning
confidence: 99%
“…Venous leg ulcers (VLUs) account for 60%‐80% of all chronic recurring leg ulcers, lasting anywhere from a matter of weeks to more than 10 years; however, prevalence varies across settings – it tends to increase with age and ranges from 0.12% to 1.03% in patients aged 70 years and over 1,2 . Management of the multiple causes of VLUs is an interdisciplinary challenge with major socio‐economic significance 3,4 . Patients with VLUs concurrently experience various psychoneurological symptoms including leg swelling, skin irritation, itchiness, pain, depression, fatigue, anxiety, and sleep disturbance 5‐8 .…”
Section: Introductionmentioning
confidence: 99%